(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
Tax compliance costs are the costs incurred by taxpayers in fulfilling their obligations according to tax rules and regulations. In an indirect tax mechanism such as GST, compliance cost is borne by GST registered companies as tax collectors at the point of sales of goods and services from consumer on behalf of the government. Tax literatures acknowledge the fact about tax compliance costs and how they burdened registered companies. Ever since the first day of implementation of GST in April 2015, the issue of the burden of tax compliance costs borne by GST registered companies has always remained a hot discussion amongst academics, politicians and businessmen. This paper examines the GST tax compliance costs incurred by registered GST companies in meeting their obligations as tax collectors from consumers to the government. This analysis is based on the experience of countries that had earlier experiences implementing GST. This paper then concludes by presenting data on the magnitude of compliance costs that are borne by the GST registered companies in those countries. This paper also shows the steps taken by the authorities in those countries to reduce the burden of tax compliance costs borne by the companies. The findings of this paper are useful for policy makers and decision makers for improvement and strengthening of policy implementation purposes.